Molecular Comparisons of Full Length Metapneumovirus (MPV) Genomes, Including Newly Determined French AMPV-C and –D Isolates, Further Supports Possible Subclassification within the MPV Genus - Brown, Paul A.; Lemaitre, Evelyne; Briand, François-Xavier; Courtillon, Céline; Guionie, Olivier; Allée, Chantal; Toquin, Didier; Bayon-Auboyer, Marie-Hélène; Jestin, Véronique; Eterradossi, Nicolas (PloS one, 2014)
Four avian metapneumovirus (AMPV) subgroups (A-D) have been reported previously based on genetic and antigenic differences. However, until now full length sequences of the only known isolates of European subgroup C and subgroup D viruses (duck and turkey origin, respectively) have been unavailable. These full length sequences were determined and compared with other full length AMPV and human metapneumoviruses (HMPV) sequences reported previously, using phylogenetics, comparisons of nucleic and amino acid sequences and study of codon usage bias. Results confirmed that subgroup C viruses were more closely related to HMPV than they were to the other AMPV subgroups in the study. This was consistent with previous findings using partial genome sequences. Closer relationships between AMPV-A, B and D were also evident throughout the majority of results. Three metapneumovirus "clusters" HMPV, AMPV-C and AMPV-A, B and D were further supported by codon bias and phylogenetics. The data presented here together with those of previous studies describing antigenic relationships also between AMPV-A, B and D and between AMPV-C and HMPV may call for a subclassification of metapneumoviruses similar to that used for avian paramyxoviruses, grouping AMPV-A, B and D as type I metapneumoviruses and AMPV-C and HMPV as type II.